Widespread Expression of the AMPA Receptor GluR2 Subunit at Glutamatergic Synapses in the Rat Spinal Cord and Phosphorylation of GluR1 in Response to Noxious Stimulation Revealed with an Antigen-Unmasking Method - Nagy, Gergely G. (J Neurosci, 2004)
Glutamate, the principal excitatory neurotransmitter in the spinal cord, acts primarily through AMPA receptors. Although all four AMPA subunits are expressed by spinal neurons, we know little about their distribution at glutamatergic synapses. We used an antigen-unmasking technique to reveal the synaptic distribution of glutamate receptor (GluR) 1-4 subunits with confocal microscopy. After pepsin treatment, punctate staining was seen with antibodies against each subunit: GluR2-immunoreactive puncta were distributed throughout the gray matter, whereas GluR1-immunoreactive puncta were restricted to the dorsal horn and were most numerous in laminas I-II. Punctate staining for GluR3 and GluR4 was found in all laminas but was weak in superficial dorsal horn. Colocalization studies showed that GluR2 was present at virtually all (98%) puncta that were GluR1, GluR3, or GluR4 immunoreactive and that most (>90%) immunoreactive puncta in laminas IV, V, and IX showed GluR2, GluR3, and GluR4 immunoreactivity. Evidence that these puncta represented synaptic receptors was obtained with electron microscopy and by examining the association of GluR2- and GluR1-immunoreactive puncta with glutamatergic boutons (identified with vesicular glutamate transporters or markers for unmyelinated afferents). The great majority (96%) of these boutons were associated with GluR2-immunoreactive puncta. Our findings suggest that GluR2 is almost universally present at AMPA-containing synapses, whereas GluR1 is preferentially associated with primary afferent terminals. We also found a substantial, rapid increase in staining for synaptic GluR1 subunits phosphorylated on the S845 residue in the ipsilateral dorsal horn after peripheral noxious stimulation. This finding demonstrates plastic changes, presumably contributing to central sensitization, at the synaptic level.